Late-Holocene and Little Ice Age palaeoenvironmental change inferred from pollen analysis, Isla de los Estados, Argentina - Ponce, Juan Federico (2017)
We present pollen and spore analysis from a peat-bog section from southwestern Isla de los Estados (Staaten Island), Tierra del Fuego to better understand late-Holocene environmental change in southernmost Patagonia. The island's position as the easternmost landmass at the southernmost of South America, places it squarely within the influence of the southern westerly winds (SWW) and the Antarctic Circumpolar Current, and so makes the island a unique location to document the palaeoecological response to climate change during the late Quaternary. We compare our Nothofagus pollen record from Bahía Franklin with other Nothofagus pollen records from Isla de los Estados and Tierra del Fuego. Nothofagus has been shown to respond to changes in mean annual temperature in the southern latitudes under cooler climate with little seasonality in precipitation. We also evaluate the correspondence between these changes in vegetation to other late-Holocene environmental proxies that include variations in sea surface temperature (SST) from the Beagle Channel and records of past glacier fluctuations. Our results show that low concentrations of Nothofagus pollen existed at Bahía Franklin at about 4000 cal yr BP. Climate ameliorated between ca. 3500 and 500 cal yr BP based on an increase in frequency and concentration values of Nothofagus and Drimys winteri. Between about 500 and 50 cal yr BP, the pollen record revealed a noticeable decline in the forest density. We interpret the decline in forest density in Isla de los Estados between 500 and ∼50 yr cal BP as a response to cold and windy conditions during the Little Ice Age (LIA). Our interpretation from our Nothofagus pollen record broadly agrees with regional cooling recorded in reconstructed SST of the Beagle Channel and with glacier expansion in the Fuegian Cordillera.